The Effect of Financial Ratios, Economic Value Added, and Market Value Added on Stock Returns of Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange - Fajar Eka Saputra; Nirmala Nirmala; Siti Muntahanah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Stock return fluctuations in the transportation and logistics sector underscore the need to identify financial and market-based factors that inform investment decision-making. This study examines the effects of Current Ratio, Return on Assets, Debt to Equity Ratio, Economic Value Added, and Market Value Added on stock returns among transportation and logistics companies listed on the Indonesia Stock Exchange during 2019–2024. A quantitative approach was employed using panel data from 11 companies selected through purposive sampling. The data were analyzed using panel data regression with the Common Effect Model in EViews 12. The findings show that Current Ratio, Return on Assets, Debt to Equity Ratio, and Economic Value Added have no significant effect on stock returns, whereas Market Value Added has a positive and significant effect. These results indicate that market-based indicators are more relevant than internal financial indicators in explaining stock return variations in the transportation and logistics sector. The study concludes that investor confidence and a firm’s capacity to create market value are key determinants of stock return performance. The findings contribute to the literature on capital market performance by emphasizing the explanatory role of market value creation and provide practical implications for firms and investors in strengthening firm value, market confidence, and evidence-based investment decisions.